Spatiotemporal variations of water levels and river-lake interaction in the Poyang Lake basin under the extreme drought - Hexiang Chen; Guangqiu Jin; Hongwu Tang; Jinran Wu; You-Gan Wang; Zhongtian Zhang; Yanqing Deng; Siyi Zhang (Journal of Hydrology: Regional Studies)
Study region: Poyang Lake, China's largest freshwater lake Study focus: The water level variations of Poyang Lake and the combined effects of the upstream rivers and the Yangtze River during extreme drought events are not yet fully understood. In this study, the temporal and spatial variations of Poyang Lake's water level and the river-lake interactions were investigated using mathematical statistics and regression models. New hydrological insights for the region: Extreme drought occurrences in Poyang Lake have increased over fourfold compared to previous periods since the 21st century. The 2022 extreme drought represents the most intense, severe, and prolonged drought event in Poyang Lake since 1956. It is characterized by unprecedented low water levels during both the flood and dry seasons. The study further emphasizes the changes in river-lake interactions during the extreme drought, indicating a reduced blocking effect of the Yangtze River on Poyang Lake during the flood season and a diminished emptying effect during the retreating and dry seasons. Compared to multi-year averages, reduced upstream discharge, Yangtze River flow, and the Three Gorges Dam operations during this drought contributed 23.68 %, 38.10 %, and 38.22 % respectively to the water level decline. During the drought period, both natural precipitation-driven flow increase in upstream rivers and water released from the dam provided short-term relief, though insufficient to fully mitigate the drought conditions.